Pediatric to Adult Epilepsy Transition in Ambulatory Care: Benefits of a Multidisciplinary Epilepsy Transition Clinic - Twanow, Jaime-Dawn E.; Maturu, Sarita; Khandker, Nabil (Journal of Pediatric Epilepsy, 2020)
Children with epilepsy comprise 3.2% of the estimated 500,000 youth with special medical needs who move from the pediatric to adult care model annually. These 16,000 children who require transfer each year represent a challenging subset of 470,000 youth living with epilepsy in the United States. Transition and transfer of care are complex and require gradual processes. This period for youth with epilepsy is often associated with inadequate follow-up and increased risk of nonadherence. Furthermore, youth and adults with epilepsy are known to have suboptimal social and emotional outcomes compared with peers, with high rates of under education, underemployment, poverty, and struggles with mental health. The goal of improving social determinants and continuity of care prompted the development of formal epilepsy transition clinics. Multiple clinic models exist, sharing the overarching goal of supporting youth while building self-management skills, tailored to age and developmental level. Early evidence shows that transition discussion leads to statistically significant increases in transfer readiness and self-efficacy in young adults with epilepsy. Our center boasts a 100% attendance rate at our transition and transfer clinic and 78% compliance with follow-up, further demonstrating that patients and families value quality transition programming.
Keywords: transition; epilepsy; multidisciplinary clinic; neurology